IMPROVING FEEDLOT EFFICIENCY AND PROFITABILITY THROUGH STRATEGIC INVESTMENT EVALUATION OF JAKARTA'S STATE-OWNED FEEDLOT - Afan Wahyu Syafii; Sylviana Maya Damayanti (CV. Radja Publika, 2026)
Indonesia meets only 55–60% of national beef demand through domestic production, with the remainder sourced from live feeder cattle imports. This paper assesses the financial viability of an integrated investment program to upgrade the physical and management capabilities of the Serang Feedlot of Perumda Dharma Jaya. As part of its role as a Regional State-Owned Enterprise of the DKI Jakarta Provincial Government, this feedlot is responsible for processing the majority of live feeder cattle imported into Indonesia. Due to high costs associated with importing live animals, it has become imperative for Indonesia to develop greater efficiency in utilizing these resources domestically. Despite being the first point of contact for all imported cattle prior to their entry into the human food chain, Indonesian feedlots have historically performed poorly compared to global averages when measured by such performance metrics as average daily weight gain (ADG), percent feed cost per head and space usage per head. The proposed combined investment program includes upgrading pens (pen expansion); total mixed ration (TMR) feeding systems (mechanizing TMR); and a feed inventory system (bulk feed storage). It is based on a 10 year financial projection of cash flows using historical operating data provided by the facility over a 3-year period. In addition to performing a traditional cost benefit analysis and Monte Carlo risk analysis of projected returns on investment (ROI), this research also performs PESTLE analyses and SWOT/TOWS strategic analyses. A total of 13 sensitivity analyses were conducted to test the impact of potential future changes in input prices and/or facility operating conditions. Under the base-case assumptions (including 60% equity and 40% loan financing structure; weighted average cost of capital 12.0%) the total investment outlay will generate a net present value of IDR 349.9 Billion and an internal rate of return (IRR) of approximately 83.97% over the 10 year planning period. Based upon the Monte Carlo simulation results there is 100% confidence level that the expected net present value will be positive. With respect to the sensitivity analyses, all thirteen possible combinations of either increased or decreased costs or reduced or enhanced operation efficiencies resulted in both positive expected values for ROI and rates of return on investment above the respective costs of capital. These results provide evidence that poor performance in this facility is due to a combination of avoidable internal factors rather than non-controllable external factors and that the application of a formalized process-based evaluation model can provide a basis for identifying feasible solutions, justifying those solutions and implementing them.